An Analysis of the Factors Influencing of Pre-service Science Teacher in Conceptualization of STEM Education: Self-Efficacy and Content Knowledge - Pramudya Dwi Aristya Putra; Nur Ahmad; Sri Wahyuni; Erlia Narulita (Postgraduate, University of Mataram, 2021)
This research investigates the factors that influence pre-service science teachers' conceptualization of STEM education. The factors involved STEM self-efficacy, STEM anxiety, science content knowledge, and mathematics content knowledge. The survey method was utilized in this research to collect a huge number of respondents at one time. The participants were 604 pre-service science teachers in Indonesia with different backgrounds (physics Education, biology education, chemistry education, Ingrate of Science education, and primary school education). The instruments were developed and share with participants using a google form to avoid the items that the participant did not fill in. The data analyzed using STEM showed that science content knowledge, STEM self-efficacy, and STEM anxiety were influencing the conceptualization of STEM education. This research suggested that to improve the quality of STEM education in the classroom. Pre-service science teachers should understand the concept of the content taught